IMPROVING GRAMMAR SKILL USING EGRA TECHNIQUE FOR THE STUDENTS’ EIGHTH GRADE AT SMPN 5 CIMAHI - Mayang Kusumastuti; Mega Pratiwi; Hendra Husnussalam (PROJECT (Professional Journal of English Education), 2019)
Grammar is one part to improve four skills that we also known. To enhance grammar skill we have to prefer the accurately method as a way in studying grammar. The researcher was chosen Exposure, Generalization, Reinforcement, and Application (EGRA) technique as a method to teaching English grammar to students’ eigtht grade at SMPN 5 Cimahi. It was arranged with using pre-experimental method, peculiarly one-group pre-test post-test design. The technique showed that can develop grammar skill students’. The average score of the test result is 40,83 for the pre-test and 71,70 for the post-test. From the result, it can determine that EGRA technique can improve grammar skill students’. Besides that, EGRA technique can build a good team work in the classroom.